Relation between hyponatraemia and falls by acute hospitalised patients: A case-control study - Aranda-Gallardo, Marta; González-Lozano, Antonio; Oña-Gil, José Iván; Morales-Asencio, José Miguel; Mora-Banderas, Ana María; Canca-Sánchez, José Carlos; González-Lozano, Antonio (Wiley, 2021)
Aims and objectives To investigate the possible association between hyponatremia and falls, in a sample of hospitalised adult patients. Background In-hospital falls are a problem of major importance, provoking a significant decline in the quality of life of many patients. Recent studies have identified a relationship between such falls and the presence of hyponatremia. Design Analytical retrospective observational case-control study. Methods The study population consisted of hospitalised patients who had suffered an in-hospital fall during the period 2014–2016. For each case, two controls who had not suffered any such fall were recruited. These cases and controls were matched according to gender, age, hospitalisation unit and date of admission. Study data were obtained from the hospital’s record of falls, regarding the patients’ socio-demographic factors, physical and psychological conditions and blood levels of sodium, potassium, urea and creatinine. The study is reported in accordance with STrengthening the Reporting of OBservational studies in Epidemiology guidelines. Results The study sample consisted of 555 patients (185 cases and 370 controls). Hyponatraemia was detected in 57 cases (30.8%). A statistically significant relationship was found between the presence of hyponatraemia and the occurrence of falls: OR = 2.04. Other risk factors for falls were hypercreatinaemia OR 2.49, hyperuraemia OR 1.82, disorientation, need for ambulatory assistance and longer hospital stay. Conclusions From the study findings, we conclude that hyponatraemia is a predictor of falls by acute hospitalised patients. Further research is needed on the relationship between hypercreatinaemia, hyperuraemia and falls. (...)
Keywords: Hospitalizados; Accidental falls; Hospitalised patients; Hyponatraemia; Nursing; Risk factors